Chapter Saramago e i valori di Sassoli: del mitico e dell'etico in Caino - Neto, Nefatalin Gonçalves (Libere carte, 2023)
Cain resumes the biblical story of the genesiacs brothers to recount it in a heterodox way. Based on the canonical biblical texts, the ethical perspective of David Maria Sassoli and in ideological discourses, José Saramago (re)reads the life of the murderous brother by a desacralizing bias, establishing a process of discursive reorganization of the Bible and, consequently, of Christianity - an ideology rooted in the social thought that the writer Portuguese intends to resolve. Our proposal is to probe such ethical assumptions questioned by the novel. Thus, we will focus on the figure of the protagonist to reflect on postures, symbolic representations, narrative functions and ideological expressiveness. Let us, through our reading, decommthe kaleidoscopic clash that the skilled narrator stages to present an ethical proposal in dialogue with renewing ideals of today's society.